2008
DOI: 10.1534/genetics.107.071332
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Estimation of Mutation Rates in a Wheat Population With a Gene Genealogy Approach

Abstract: Microsatellite markers are extensively used to evaluate genetic diversity in natural or experimental evolving populations. Their high degree of polymorphism reflects their high mutation rates. Estimates of the mutation rates are therefore necessary when characterizing diversity in populations. As a complement to the classical experimental designs, we propose to use experimental populations, where the initial state is entirely known and some intermediate states have been thoroughly surveyed, thus providing a sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 64 publications
2
18
0
Order By: Relevance
“…The Ne value for the in situ population was similar to those observed in experimental populations of another autogamous species (i.e. wheat) that were multiplied ex situ for 10-15 generations sowing a similar number of plants as sown by farmers for this landrace (Goldringer et al 2001;Raquin et al 2008). In contrast, Ne values after one or two generations of ex situ multiplication were ten times lower than the Ne value Fig.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The Ne value for the in situ population was similar to those observed in experimental populations of another autogamous species (i.e. wheat) that were multiplied ex situ for 10-15 generations sowing a similar number of plants as sown by farmers for this landrace (Goldringer et al 2001;Raquin et al 2008). In contrast, Ne values after one or two generations of ex situ multiplication were ten times lower than the Ne value Fig.…”
Section: Discussionsupporting
confidence: 77%
“…As commonly found (Frankham 1995;Goldringer et al 2001;Raquin et al 2008), the estimated effective size was much smaller than the demographic effective size based on the true number of plants cultivated in each generation.…”
Section: Discussionmentioning
confidence: 59%
“…Conversely, 31 markers were polymorphic in the evolved population but not among the parents. This could be explained by (i) alleles specific of the four lines missing from our parental panel, (ii) alleles lost for some parental lines during the management procedure in genebanks (regeneration through selfing cycles; Esquinas-Alcazar 2005), as they could have presented initial residual heterozygosity, (iii) contamination (migration) despite the isolation of plots (Hucl and Matus-Cadiz 2001), and (iv) mutation, as found for SSR markers in another wheat experimental population (Raquin et al 2008). The observed heterozygosity in the evolved population was 3.2%.…”
Section: Evolution Between the Initial And The Evolved Populationsmentioning
confidence: 97%
“…But since it's an interspecific and interploidy cross, with a high level of progeny heterozygosity, and the molecular markers were the hypervariable microsatellites, it's not such a surprise when novel alleles present. It's considered that the instability of the simple repeats are mainly caused by the unequal crossing over during recombination and polymerase slippage during DNA replication (Sia et al 1997;Raquin et al 2008), and the allele mutations or variations of the SSR loci is correlated both with the high heterozygosity and the presence of multiple alleles (Vigouroux et al 2002;Ellegren 2004). It's suggested that six of the seven SSR loci in present study had null alleles as have been reported in Actinidia by Fraser et al (2005).…”
Section: Discussionmentioning
confidence: 99%